Loan-to-Deposit Ratio Analysis Before and During the COVID-19 Pandemic - Xenaneira SHODROKOVA; Imam ASNGARI; Ariodillah HIDAYAT (Management and Economics Review, 2023)
The banking sector contributes to the pace of the economy. Since the increasing outbreak of the COVID-19 virus, there are many risks that banks will face, such as bad loans as measured by the Non-Performing Loan (NPL) ratio, a decrease in net interest margin as measured by the Net Interest Margin (NIM) ratio, increasing Operating Costs to Operating Income (BOPO), and increasing Third Party Funds (DPK) but not followed by high lending. This disrupts the balance between loans and deposits, measured through the Loan-to-Deposit Ratio (LDR). In this study using secondary data types in the form of data on the highest Core Capital Bank Group (BUKU IV) in Indonesia, using quarterly data for the 2018-2021 period using the Fixed Effect Model method. This data is obtained from the website of the Financial Services Authority (OJK) Indonesia, and Worldometer. The purpose of this study was to analyze the effect of the NPL, NIM, BOPO, and Dummy COVID-19 variables on LDR. The results showed that during the COVID-19 pandemic, the NIM and BOPO variables had a positive and significant effect while the NPL and Dummy Covid variables showed a negative and significant relationship to the Loan-to-Deposit Ratio (LDR).